2006
DOI: 10.1111/j.1748-8583.2006.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Employers' attitudes, practices and policies towards older workers

Abstract: Despite policy emphasis on the importance of older workers (i.e. those aged 50 and above) to current and future labour markets, relatively little is known about the ways in which employers' attitudes, policies and practices influence their recruitment and retention. Drawing upon previous work by Taylor and Walker, this article reports qualitative research among employers across Scotland, which sought to investigate further the relationships between employers' policies, practices and attitudes towards older wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
266
1
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(293 citation statements)
references
References 16 publications
(21 reference statements)
14
266
1
12
Order By: Relevance
“…In 2011, following a series of legal challenges, the default retirement age of 65 was abolished, effectively outlawing mandatory retirement unless the employer can provide a legally justifiable reason (see below). Moreover, even before the legislative changes, throughout the 2000s the 'business case' for employing older people was achieving more coverage, linked to debates about the benefits of organisational diversity (Lain, 2012;Loretto and White, 2006). There is reason to believe that recent increases in the employment of over-65s likely to become a long term trend.…”
Section: The Changing Landscape For Over-65s In the Uk Labour Marketmentioning
confidence: 99%
“…In 2011, following a series of legal challenges, the default retirement age of 65 was abolished, effectively outlawing mandatory retirement unless the employer can provide a legally justifiable reason (see below). Moreover, even before the legislative changes, throughout the 2000s the 'business case' for employing older people was achieving more coverage, linked to debates about the benefits of organisational diversity (Lain, 2012;Loretto and White, 2006). There is reason to believe that recent increases in the employment of over-65s likely to become a long term trend.…”
Section: The Changing Landscape For Over-65s In the Uk Labour Marketmentioning
confidence: 99%
“…Analysis of surveys conducted in Denmark, France, Germany, Italy, the Netherlands, Poland, Sweden, and the UK in 2009 suggests that employers retain rather than hire older workers (Conen et al 2012). Loretto and White's (2006) interviews with Scottish employers found that despite having some positive attitudes towards older workers in terms of their reliability and work effort, their preferred recruits were younger. Qualitative research with 56 older people in the North of England has also identified higher levels of perceived age discrimination by employers, and devaluing of experience (Porcellato et al 2010;Carmichael et al 2011).…”
Section: Constraints and Limitations Of Policies To Extend Working Lifementioning
confidence: 99%
“…In the meta-analysis of opinions about older workers, age negatively correlated with the assessment of many skills, productive potential and productivity (Bal et al 2011). Negative age stereotypes can significantly influence employers' decisions that are unfavourable for older workers and set a barrier for increasing employability and retention in older groups (Perry and Finkelstein 1999;Bytheway 2005;Loretto and White 2006;OECD 2006). Positive opinions about older workers, meanwhile, do not often translate into supportive practices (Taylor and Walker 1998).…”
Section: Soft Discrimination As Work-related Basis For Hard Discriminmentioning
confidence: 99%